BUILDING A SUSTAINABLE FUTURE: A LITERATURE REVIEW ON CIRCULAR ECONOMY IMPLEMENTATION - Moh. Yamin Darsyah; Caroline Caroline; Redi Yana Kapisa (RADJA PUBLIKA, 2025)
The implementation of a circular economy is at the forefront of global efforts to create a sustainable future. The circular economy aims to maximise the efficiency of material and energy flows by replacing the linear 'take, make, dispose' model with one that supports reuse, repair and recycling. This literature review explores the key success factors, key challenges, and potential benefits of implementing a circular economy. The findings show that multi-stakeholder engagement, supportive policies, as well as technological innovation and product design are critical for successful implementation. However, barriers such as limitations in product design, inadequate infrastructure, and lack of public awareness are challenges that must be overcome through cross-sector collaboration. The study also highlights the contribution of the circular economy to the achievement of sustainable development goals, including the creation of new jobs and driving innovation. With an integrative and strategic approach, the circular economy has the potential to be an important step in addressing global environmental challenges.